Role of Interleukin-6 in the Radiation Response of Liver Tumors - Chen, Miao-Fen; Hsieh, Ching-Chuan; Chen, Wen-Cheng; Lai, Chia-Hsuan (International journal of radiation oncology, biology, physics, 2012)
To investigate the role of interleukin (IL)-6 in biological sequelae and tumor regrowth after irradiation for hepatic malignancy, which are critical for the clinical radiation response of liver tumors. The Hepa 1-6 murine hepatocellular cancer cell line was used to examine the radiation response by clonogenic assays and tumor growth delay in vivo. After irradiation in a single dose of 6 Gy in vitro or 15 Gy in vivo, biological changes including cell death and tumor regrowth were examined by experimental manipulation of IL-6 signaling. The effects of blocking IL-6 were assessed by cells preincubated in the presence of IL-6–neutralizing antibody for 24 hours or stably transfected with IL-6–silencing vectors. The correlations among tumor responses, IL-6 levels, and myeloid-derived suppressor cells (MDSC) recruitment were examined using animal experiments. Interleukin-6 expression was positively linked to irradiation and radiation resistance, as demonstrated by in vitro and in vivo experiments. Interleukin-6–silencing vectors induced more tumor inhibition and DNA damage after irradiation. When subjects were irradiated with a sublethal dose, the regrowth of irradiated tumors significantly correlated with IL-6 levels and MDSC recruitment in vivo. Furthermore, blocking of IL-6 could overcome irradiation-induced MDSC recruitment and tumor regrowth after treatment. These data demonstrate that IL-6 is important in determining the radiation response of liver tumor cells. Irradiation-induced IL-6 and the subsequent recruitment of MDSC could be responsible for tumor regrowth. Therefore, treatment with concurrent IL-6 inhibition could be a potential therapeutic strategy for increasing the radiation response of tumors.